The Sauna and health: How regular sauna sessions affect the body’s health - Łagowski, Ryszard; Kosęda, Julia; Fordymacki, Jacek (Quality in Sport, 2024)
Sauna use, practiced for thousands of years, has its roots in Finnish culture, where it was considered an essential part of health and hygiene. In recent years, a growing body of scientific research has confirmed the numerous health benefits associated with regular sauna use. This research review focuses on the effects of sauna sessions on the body’s health, with particular emphasis on the cardiovascular system, blood pressure, respiratory system and urinary system. Analyses show that regular sauna use contributes to lowering the risk of cardiovascular disease by reducing blood pressure and improving the lipid profile. In addition, sauna has a beneficial effect on lung function, reducing the risk of diseases such as chronic obstructive pulmonary disease and pneumonia. It is also worth noting that sauna baths are safe for patients with kidney disease, as confirmed by research results. These indications underscore the importance of regular sauna sessions as a form of health support, helping to improve quality of life and long-term well-being.